HUBUNGAN STRES DENGAN KEJADIAN GASTRITIS PADA REMAJA KELAS XI IPA DI SMA NEGERI 9 MANADO (JURNAL KEPERAWATAN, 2014)
Abstract: Anyone can experience stress, not only adults, but teens can also experience stress. Adolescence is a time of emotional turmoil and imbalance. Stress has a negative effect through the digestive tract neuroendocrine mechanisms that are at risk for experiencing gastritis. The purpose of this study was to determine the relationship of the incident stress gastritis in adolescents class XI Science SMAN 9 Manado. The samples used were 61 respondents. Data was collected through questionnaires using the DASS (Depression Anxiety Stress Scales) that has been modified and tested validity. The research design used was a cross sectional study. Research results obtained show that there is a correlation with the incidence of stress gastritis in adolescents, with a result of 0.001. The conclusion of this study means that Ho is rejected which states that there is a significant correlation between the incidence of stress gastritis with results p value